A water and greenhouse gas inventory for hygroscopic building-scale cooling tower operations. (15th June 2022) - Nugent, Jenni; Lux, Scott M.; Martin, Christopher; Stillwell, Ashlynn S.
Abstract: Heating, ventilation, and air conditioning (HVAC) systems for large buildings often use water for cooling. The U.S. Department of Defense funded the demonstration of a novel hygroscopic HVAC cooling tower technology with the goal of reducing water usage. We quantified direct and indirect water usage and greenhouse gas (GHG) emissions to analyze the tradeoffs associated with transitioning from a conventional wet-cooling HVAC tower to the hygroscopic system. We quantified GHG emissions for electricity consumed directly by the building-scale cooling system and the indirect electricity associated with water and wastewater conveyance and treatment. We found that the GHG emissions impact of increased electricity consumption in the building-scale cooling system is greater than the GHG emissions impact of indirect energy savings from the decrease in water usage, resulting in a net increase in GHG emissions. The indirect water consumption associated with cooling water for electricity generation was comparatively low when compared to direct water usage volumes that were reduced by switching to the hygroscopic system. The hygroscopic system showed promising water savings ability that is best suited to regions with extreme water scarcity, high water sourcing and treatment energy intensity, and/or when the electricity is sourced from low-carbon sources. Highlights: Hygroscopic cooling towers are an alternative to evaporative cooling. The hygroscopic technology effectively reduced water requirements. Additional operational electricity increases net greenhouse gas emissions. Tradeoffs exist between water usage and emissions for building cooling towers. Hygroscopic systems are suitable for arid areas and low-carbon electricity.